2006
DOI: 10.1063/1.2168037
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magnetic properties of Ni nanoparticles in rutile formed by Ni ion implantation

Abstract: Optical properties and structure characterization of sapphire after Ni ion implantation and annealing J. Appl. Phys. 98, 073524 (2005); 10.1063/1.2084314 An aerosol-mediated magnetic colloid: Study of nickel nanoparticles J. Appl. Phys. 98, 054308 (2005); 10.1063/1.2033145 Optical properties of metallic nanoparticles in Ni-ion-implanted α-Al 2 O 3 single crystals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…In contrast, Cho et al, questioned the origin of the ferromagnetism in Ni doped TiO 2 by compositional analysis and transport measurements, 21 while Zhu et al reported Ni-nanoparticle formation in rutile TiO 2 . 22 In the present paper, we attempt to clarify the ferromagnetism in Ni implanted ZnO. X-ray diffraction ͑XRD͒ and zero field cooled magnetization/field cooled magnetization ͑ZFCM/FCM͒ were used to investigate the structural and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Cho et al, questioned the origin of the ferromagnetism in Ni doped TiO 2 by compositional analysis and transport measurements, 21 while Zhu et al reported Ni-nanoparticle formation in rutile TiO 2 . 22 In the present paper, we attempt to clarify the ferromagnetism in Ni implanted ZnO. X-ray diffraction ͑XRD͒ and zero field cooled magnetization/field cooled magnetization ͑ZFCM/FCM͒ were used to investigate the structural and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic moment of clusters is found to be higher than that of the bulk while that of nanoparticles is found to be lower than that of the bulk. [5][6][7][8][9][10][11][12][13][14] The saturation magnetization M S and the coercivity of Ni nanoparticles reported in literature vary from 15 to 46 emu g −1 and from 20 to 400 Oe, respectively. The variation in these magnetic parameters is due to the different synthesis techniques used and the nature of encapsulation of the Ni particles.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason is that the behavior of nanodimensional objects can strongly differ from the macroscopic ones due to a large surface to volume ratio. Currently, there is a great deal of interest to incorporate magnetic nanoparticles into insulator and semiconductor materials to form nanocomposites, which shows interesting magnetic, optical and magnetoelectric properties [7][8][9][10][11][12][13][14][15][16][17][18]. The nanocomposite system can be potentially used for ultrahigh density data storage devices as well in magnetooptic and magnetotransport systems.…”
Section: Introductionmentioning
confidence: 98%